2007
DOI: 10.1037/0096-1523.33.6.1352
|View full text |Cite
|
Sign up to set email alerts
|

Trade-offs between gaze and working memory use.

Abstract: Eye movements during natural tasks suggest that observers do not use working memory to capacity but instead use eye movements to acquire relevant information immediately before needed. Results here however, show that this strategy is sensitive to memory load and to observers' expectations about what information will be relevant. Depending upon the predictability of what object features would be needed in a brick sorting task, subjects spontaneously modulated the order in which they sampled and stored visual in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
101
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(116 citation statements)
references
References 81 publications
15
101
0
Order By: Relevance
“…Comprehending a long, complex sentence-the kind of sentence on which readers are likely to regress-loads WM. Droll and Hayhoe (2007) measured eye movements during a sorting task and found that when WM load was high, participants tended to switch from holding the positions of bricks in WM to repeatedly seeking them with eye movements. Irwin and Zelinsky (2002) found that their participants could remember the locations of only three to five objects in WM; reading a sentence typically requires many more fixations than this, so perhaps it is not surprising that readers prefer to reread information, rather than using a memory-based strategy, for ambiguity resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehending a long, complex sentence-the kind of sentence on which readers are likely to regress-loads WM. Droll and Hayhoe (2007) measured eye movements during a sorting task and found that when WM load was high, participants tended to switch from holding the positions of bricks in WM to repeatedly seeking them with eye movements. Irwin and Zelinsky (2002) found that their participants could remember the locations of only three to five objects in WM; reading a sentence typically requires many more fixations than this, so perhaps it is not surprising that readers prefer to reread information, rather than using a memory-based strategy, for ambiguity resolution.…”
Section: Discussionmentioning
confidence: 99%
“…If, as found by Furneaux and Land (1999), expertise allows more information to be held in a visuo-motor buffer, it may also be the case that experts here were able to hold more information in visual memory as events unfolded. Because of this, they may have had to use fewer fixations to regain lost information in the manner shown to occur under high load by Droll and Hayhoe (2007) and Hardiess, Gillner and Mallot (2008).…”
Section: Discussionmentioning
confidence: 99%
“…the magnitude of the visual-motor buffer was not affected by expertise, though experts could fit more information into the buffer. Others have shown that fixation patterns are dependent on the cognitive complexity and working memory load required to perform a task, such that fixations can be used to regain task-relevant information (Droll & Hayhoe, 2007;Hardiess, Gillner & Mallot, 2008). It seems reasonable that in a more cognitively demanding task, expertise may moderate the cognitive and mnemonic load for observers and so affect the lag.…”
Section: Introductionmentioning
confidence: 99%
“…This result argues elegantly that whether information about the height of the brick was retained stably throughout the task depended critically on whether and when the height was relevant to the task. The importance of task relevance through time in representations for visuomotor tasks was explored further by Droll & Hayhoe [55] in which the predictability that a cue would be relevant later in the block-sorting task was varied. In this paradigm, blocks were defined by four properties: height, width, colour and texture (figure 5).…”
Section: Memory During Manipulations In Proximate Spacementioning
confidence: 99%